Love Unites Us in Our Differences, Faith Determines Our Path: Individual Decision-Making in Interfaith Dating Relationships - Lubis, M. Andri Yansah; Pratama, Mario; Santoso, Indriyani (In Trend : International Journal of Trends in Global Psychological Science and Education, 2024)
The purpose of this research is to describe the decision-making dynamics of individuals in interfaith dating relationships. The study employs a qualitative methodology with a phenomenological approach. Three participants were involved in semi-structured interviews. Data were analyzed using Interpretative Phenomenological Analysis (IPA) to understand the unique experiences of each individual. The results identified 13 main themes in the decision-making process: relationship motives, environmental response, negative emotions, challenges and issues, coping strategies, social support, romantic belief, commitment, understanding, religiosity, compromise, hope, and relationship satisfaction. The decision-making dynamics are divided into three main stages: pre-dating, dating, and relationship continuation. Each stage highlights the importance of understanding, adjustment, and effective coping strategies to face challenges and build a strong and harmonious relationship despite religious differences.